Analisis Pemanfaatan Mobile Commerce untuk Penjualan Kartu Operator di Grapari Telkomsel Bali - Iwan Setiawan; Aditya Faqih Ramadhani M; I Made Acharya Deva A (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Mobile commerce has become a crucial element in the business world, opening up new opportunities to increase efficiency and effectiveness in operator card sales. This research aims to investigate the extent to which the use of mobile commerce can be applied to improve operator card sales performance. Research methods include customer surveys, transactional data analysis, and interviews with relevant stakeholders. Data was collected to evaluate mobile commerce adoption, factors influencing usage, and its impact on increasing operator card sales. The research results show that the use of mobile commerce has significant potential to optimize the operator's card sales process. Factors such as user convenience, transaction security, and accessibility of product information play an important role in the acceptance of this technology. By implementing mobile commerce effectively, companies can expand market share, increase customer satisfaction, and achieve sustainable business growth. These findings provide strategic insight for developing business models that are more adaptive to mobile commerce trends. Practical implications of the research results are also discussed, providing guidance for telecommunications companies and operator card providers in increasing the use of mobile commerce as an innovative sales strategy.